Susceptibility of global HIV-1 clinical isolates to fostemsavir using the PhenoSense® Entry assay. (30th November 2020) - Gartland, Margaret; Zhou, Nannan; Stewart, Eugene; Pierce, Amy; Clark, Andrew; Ackerman, Peter; Llamoso, Cyril; Lataillade, Max; Krystal, Mark
Abstract: Background: Fostemsavir is a prodrug of a first-in-class HIV-1 attachment inhibitor, temsavir, that binds to gp120 and blocks attachment to the host-cell CD4 receptor, preventing entry and infection of the target cell. Previous studies using a limited number of clinical isolates showed that there was intrinsic variability in their susceptibility to temsavir. Objectives: Here, an analysis was performed using all clinical isolates analysed in the Monogram Biosciences PhenoSense ® Entry assay as part of the development programme. Methods: In total, 1337 individual envelopes encompassing 20 different HIV-1 subtypes were examined for their susceptibility to temsavir. However, only seven subtypes (B, C, F1, A, [B, F1], BF and A1) were present more than five times, with subtype B (881 isolates) and subtype C (156 isolates) having the largest numbers. Results: As expected, variability in susceptibility was observed within all subtypes. However, for the great majority of these viruses, temsavir was highly potent, with most viruses exhibiting IC50 s <10 nM. One exception was CRF01_AE viruses, where all five isolates exhibited IC50 s >100 nM. For the 607 isolates where tropism data were available, geometric mean temsavir IC50 values were remarkably similar for CCR5-, CXCR4- and dual mixed-tropic envelopes from infected individuals. Conclusions: These data show that HIV-1 viruses from most subtypes are highly susceptible to temsavir and that temsavir susceptibility is independent of tropism.